O dispositivo inquisitivo : entre a ostentação penal e a estética política do processo penal - Amaral, Augusto Jobim do (2014)
It would not be objectionable to define the current phase of human development as a moment of vast proliferation of devices. In order to do so, more than necessarily identify perennial lines of inquisitorial tension within the dynamics of the criminal proceedings and punishment, one must define the way which it operates, how it works, what is its function, what it conveys, creates, governs the actions and thoughts, a network built amongst heterogeneous elements which have a strategic function inscribed in the crossroads of the power-knowledge relations - in short, it is suitable to properly elaborate on the operation of what might be called an inquiring device. A philosophy of devices in the field of criminal science, in particular on the life governed by the criminal justice index (and beyond), convenes a chain of interrelated variables that produce certain power and rupture threads. On the fringes, because it is in these connections between violence and law that the historical and political corpus of the inquiring source rests. Thus, to extract unprecedented novelties off the sovereign (procedural) criminal power, it appears, initially, suitable to investigate the lines of enunciation and light that let themselves be cast over a wide object on the field of inquisitorial gears. The other side of this framework shall be given at the prospect of talking about a differentiating module of the inquisitorial power. Advancing on the historicity of the source, in diachronic time, one queries about the core of punishment (the penalty) and its discourses of legitimation, which defer power strategies currently guided by security-populist ordeals in place of a repressive democracy. In a final stage, the gamut of variations of the type of dominant strategy outlined above could also be addressed from the (political) mechanism of evidence. In order to achieve this, the microcosm of the inquiring device can be poured from the open space through the procedural reforms in Brazil, where its splinters are presented, primarily, providing escape threads tensioning the very own accusatory performance in a context of democraticity. Nonetheless, from openings toward a future point of resistance, new regimens are proposed, at a risk, for a new aesthetics of the criminal proceedings.